Formulation and Physical Evaluation of the Combination Syrup of Rosella (Hibiscus sabdariffa L.) and Lemongrass (Cymbopogon citratus) - Pratiwi, Pramita Yuli; Sari, Putri Nata; Indarto, Indarto; Kirwanto, Agus (Jurnal Kebidanan dan Kesehatan Tradisional, 2023)
Background: Rosella flowers and lemon grass are combined into one formulation, namely syrup. The syrup is a concentrated preparation made from a mixture of water and sugar with a minimum sugar solution content of 65%. Previous research has never examined the formulation and physical evaluation of rosella and lemongrass syrup. The benefits of this rosella and lemongrass combination syrup are to maintain the body's immune system, reduce high blood pressure, as a source of body antioxidants. The purpose of this study was to determine the formulation and evaluation test of formulation one and formulation two on rosella (Hibiscus sabdariffa L.) and lemon grass (Cymbopogon citratus) combination syrup preparations.  Methods: The type of research used is quantitative with a descriptive design. The syrup was made with two formulations using the boiling method with the composition of rosella, lemon grass, sucrose, and distilled water. The physical test for the syrup included the viscosity test, the pH test, the organoleptic test, and then the hedonic test which included color, smell, taste, and aroma. The research was conducted at the Laboratory of Indonesia Traditional Herbals Department, Surakarta Health Polytechnic.  Results: The results of the viscosity test on the combination of rosella and lemon grass syrup were that in formula one it was 1.39 mPas and in formula two it was 1.27 mPas. The results of the pH test on formula one were 2.47 and on formula two 2.48. The results of the organoleptic syrup test for the combination of rosella and lemongrass in Formula One had a deep brown-red color, a distinctive smell of rosella and lemongrass, and a sweet and sour taste. Formula two has a red-brown color with a distinctive rosella odor and has a sweet-sour taste. The hedonic test which has the most favorable results is the formula for two aromas 67%, taste 74%, color 80%, and texture 77%.  Conclusion: The viscosity value of the two formulas is quite low and the pH of the two formulas is also low, which is less than pH 4. The taste, aroma, and texture of Formula 2 are preferred. While the colors of the two formulas produce the same percentage of preference. Recommendations for this study need to be carried out further research by changing the composition variations of rosella and lemongrass in order to obtain a pH that is in accordance with the standard.equations.